Socio-economic aspects of assistance to the military and their family members in war and post-war time - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2023)
The article is dedicated to the formation of new scientific solutions for finding ways to increase the efficiency, effectiveness and inclusiveness of social and economic assistance for the military and their family members in the war and post-war period. It has been proven that the critical problem and challenge that will accompany the development of the national socio-economic system in the coming decades is economic adaptation and social assistance to the military and members of their families. The aim of the article is to develop a set of measures and tools for socio-economic support and adaptation of military personnel and their family members during Ukraine’s war against russia and after its end. Methodology: a set of general and special methods has been used at the empirical and theoretical levels, such as the abstraction method for selecting areas of assistance to the military and their family members; methods of analysis and synthesis to build a matrix of providing social and economic assistance to various categories of the military and their family members; a comparison method for determining subjects which can be involved in delivering social and/or economic assistance to the military and their family members; methods of systematization, grouping, and logical generalization for systematization of information, formation of conclusions and scientific proposals of the article. The article uses system-functional, historical, and systemic approaches in revealing and solving the problems of providing assistance to the military and members of their families during the war and post-war period in Ukraine. Results: key opportunities for delivering social and economic assistance to the military and their family members in the war and post-war time, taking into account the objective difficulties of the state and local authorities to provide such assistance, have been identified. JEL Classification: Н80, О15.